Natural organic matter alters size-dependent effects of nanoCuO on the feeding behaviour of freshwater invertebrate shredders - Pradhan, Arunava (2015)
Nanoparticle size and the presence of natural organic matter (NOM) may influence the toxicity of nanoCuO to aquatic biota, but their interactive effects have been poorly investigated. We examined the feeding behaviour of the invertebrate shredder Allogamus ligonifer when exposed to sublethal concentrations of nanoCuO (50 and 100 mg L-1) with three particle sizes (12, 50 and 80 nm) in the absence or presence of humic acid (HA, 100 mg L-1) as a proxy of NOM. We further examined the ability of invertebrates to recover from the stressors. In the absence of nanoCuO and HA, the feeding rate of shredders was 0.416 mg leaf DM mg(-1) animal DM day(-1). The exposure to increased nanoCuO concentrations inhibited the feeding rate and effects were stronger as nanoparticle size decreased (up to 83.3% inhibition for 12 nm particles). The exposure to HA alone inhibited the feeding activity by 52.7%. However, the co-exposure to nanoCuO and HA alleviated the inhibitory effects promoted by smaller and medium sized nanoCuO (up to 29.5%). The recovery of feeding activity by the shredders after stress removal was very low; maximum recovery (16.7%) was found for invertebrates rescued from pre-exposure to lower concentration of nanoCuO with larger size. (C) 2015 Elsevier B.V. All rights reserved.